Penggunaan Katalis Fly Ash Yang Diimpregnasi Dengan CaO Dari Ca(NO3)2 Pada Tahap Transesterifikasi Minyak Sawit Off-Grade Menjadi Biodiesel - Nugraha, Putra Zelly; Helwani, Zuchra; Saputra, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The synthesis of biodiesel from off-grade palm oil needs the help of CaO/fly ash during the transesterification step. CaO with high basicity and acts as a good catalyst. The use of fly ash as the support of CaO catalyst has several benefits because it is safe for the environment, it adds economical value, and Ca inside the fly ash itself can be utilized. The synthesis of biodiesel in this research aims to observe the effect of reaction temperature, molar ratio of methanol : oil, and the effect of CaO/fly ash concentration towards biodiesel yield. The synthesis of biodiesel is performed through esterification reaction to reduce the amount of free fatty acid content in oil, and is continued by transesterification reaction to produce biodiesel. Data processing in this research is conducted using Response Surface Methodology (RSM) with the help of Design Expert 7.0 software, while experimental design is determined using Central Composite Design (CCD) which consists of 3 variables. The highest biodiesel yield is 61.72% with a reaction temperature of 60oC, methanol : oil ratio of 8:1, and CaO/fly ash catalyst concentration of 7 %wt. Biodiesel characteristics which consist of density, kinematics viscosity, acid value and flash point is consistent with Indonesia’s National Standards (SNI) of biodiesel. The variable which has the highest effect towards biodiesel yield is catalyst concentration.Key words : Biodiesel, Off-grade Palm Oil, Catalyst, Fly Ash, Transesterification.